A study on the effectiveness of task manager board game as a training tool in managing project - Mohd Yusof, Shahrul Azmi; Md Radzi, Shanizan Herman; Syed Din, Sharifah Nadera; Khalid, Nurhafizah (IP Publishing LLC, 2016)
Nowadays, games have become one of the useful tools in training.Many instructors choose to use games to enhance the way of delivering the subject.Failure to apply the suitable tool in training will lead to discouragement in learning and causing waste to the resources.An effective game will help the student understand the concept quickly. It can also help students to get involve in experiential learning where the student can manage and solve the problem as in the actual situation.This study will focus on the effectiveness of board game as a training tool for managing projects. This game has 4 tasks to be completed by students.They will be divided into a group of 4 or 5.Two methods are used in this study, pilot test, and post-test.These methods are chosen to analyze the effectiveness of using Task Manager Board Game as a teaching tool and the improvement of student’s knowledge in project management.Three sub-components assessed were motivation, user experience and learning using case studies on Kirkpatrick’s level one base on the perception of the students. The result indicated that the use of Task Manager board game as a training tool for managing project has a positive impact on students.It helps students to experience the situation of managing projects.It is one of the easiest ways for improving time management, human resources and communication skill.